Incidence and prevalence of mucopolysaccharidosis type 1 in the Irish republic. Issue 1 (7th May 2008) - Murphy, A M; Lambert, D; Treacy, E P; O'Meara, A; Lynch, S A
Abstract : Mucopolysaccharidosis type 1 (MPS1) is an autosomal recessive disorder with severe, moderate and mild phenotypes: Hurler, Hurler-Scheie and Scheie syndromes. We estimated incidence (2001–2006) and prevalence (2002 census) of MPS1 in the Irish Republic (ROI) using population data, database and chart review of all live MPS1 patients attending two specialised centres. Patient genotypes, ethnicity, province of origin, age at diagnosis and presenting features were recorded. Thirty-one patients (14 females, 17 males) were alive, 27 of whom were <15 years. Twenty-six patients had Hurler syndrome, four had Hurler-Scheie and one had Scheie syndrome. The birth incidence was 1 in 26 206 births with a carrier frequency of 1 in 81. Of note, 19/26 (73%) Hurler patients were Irish Travellers. Amongst Irish Travellers the incidence was 1 in 371 with a carrier frequency of 1 in 10. This is the highest recorded incidence worldwide. Given the morbidity and mortality associated with delayed treatment we recommend targeted newborn screening for this population.